Financial Literacy, Self Efficacy, dan Self Esteem Terhadap Perilaku Manajemen Keuangan Pada Pelaku UMKM dengan Gender Sebagai Variabel Moderasi - Wardani, Ni Putu Ika Saraswati; Suryani, Embun; Nugraha, I Nyoman (Yayasan Pendidikan Intan Cendekia, 2022)
Financial Literacy is a combination of awareness, knowledge, skills, attitudes, and behaviors needed to make good financial decisions and ultimately achieve Financial Wealth Behavior. The purpose of this study was to determine the effect of financial literacy, self-efficacy, and self-esteem on financial management behavior in MSME actors with gender as a moderating variable. This research uses associative research method. The sample in this study amounted to 100. The instrument used in this study was a questionnaire. Data were analyzed using multiple regression with the help of Partial Least Square (PLS) program. Based on the results of the study, it can be concluded that there is an influence of Financial Literacy on Financial Management Behavior on MSME actors, with a p value of 0.028 with a t statistic of 2.202. There is an influence of Self Efficacy on Financial Management Behavior in MSME actors, with a p value of 0.023 with a t statistic of 2.268. There is an effect of Self Esteem on Financial Management Behavior in MSME actors, with a p value of 0.000 with a t statistic of 7.564. Gender is not able to moderate the influence of Financial Literacy on Financial Management Behavior on MSME actors, with a p value of 0.900 with a t statistic of 0.126. Gender is not able to moderate the effect of Self Esfficacy on Financial Management Behavior on MSME actors, with a p value of 0.736 with a t statistic of 0.337. Gender is not able to moderate the influence of Self Esteem on Financial Management Behavior on MSME actors, with a p value of 0.439 with a t statistic of 0.775